Coral Reef Status after the 2018 Sunda Strait Tsunami Using the CPCe Program: A Case Study of Tanjung Lesung Banten - Anzani, Luthfi; Minsaris, La Ode Alam; Wilujeung, Alya Dina; Rahardjo, Cakra; Hasidu, La Ode Fajar; Nugroho, Fajar (Fakultas Perikanan dan Kelautan Universitas Riau, 2023)
Tsunami that swept the Tanjung Lesung coast in 2018 caused Anak Krakatau to collapse in Sunda Strait which hit the coastal areas of Banten and Lampung. Tanjung Lesung is one of the worst areas affected. Tsunami in Tanjung Lesung has taken lives, damaged infrastructure, and caused terrible natural damage. One of the damages affecting residents' lives in the Tanjung Lesung coastal community is exposure to the marine ecosystem. The main ecosystem that has the highest productivity level is the coral reef. Coral biota is the main benthic biota of reefs that are directly affected by earthquakes and tsunamis. However, until now there has been no data on the status of coral reefs after the 2018 Sunda Strait tsunami. Therefore, researchers feel the urgency of this research is high enough to determine the condition of coral reefs after the Sunda Strait tsunami in Tanjung Lesung. There are 3 research stations for data collection before the tsunami, and we conduct research in those 3 stations again after the tsunami. Then we added 3 research stations again, so there are 6 research stations. Observation of coral reefs uses the Line Intercept Transect (LIT) method. The line transect is made by stretching a roll meter with a scale parallel to the coastline along 25 meters with three replications with an interval of about 0-5 meters between replications so the total observed transect was 75 meters. The deterioration of coral reef conditions at three research stations (1-3) proved that the tsunami waves affected the damage to coral reefs. This has an impact on the diversity of coral reef species inhabitants that have decreased. Disturbance form coral-damaged structure and composition changes of the base substrate as habitat can have an impact on reef fish and coral reef inhabitants. So that this research is expected to be a reference for policymakers in determining rehabilitation steps for areas affected by the 2018 Sunda Strait tsunami.